Factors impacting length of stay and survival in patients with advanced gynecologic malignancies and malignant bowel obstruction. Issue 5 (28th January 2021) - Tigert, Melissa; Lau, Christine; Mackay, Helen; L'Heureux, Stephanie; Gien, Lilian T.
Abstract : Objectives: Malignant bowel obstruction in patients with gynecologic malignancies can impose a large symptomatic burden. The objectives of this study were to identify factors associated with shorter length of hospital stay and overall survival in gynecologic oncology patients with malignant bowel obstructions. Methods: A retrospective chart review was performed from December 2014 to March 2019 on patients admitted to a tertiary care center with a malignant bowel obstruction and advanced gynecologic malignancy. Data collection included patient and tumor characteristics, malignant bowel obstruction management (such as conservative management with bowel rest, nasogastric tube, pharmacotherapy or active intervention with surgery, chemotherapy, radiation, total parenteral nutrition or interventional stents), length of hospital stay, and survival outcomes. Statistical analysis included comparisons with Student's t-test and χ 2 test, multivariable analysis, and survival analysis. Results: A total of 107 patients with gynecologic cancer with malignant bowel obstruction were included. The majority of patients (63%, n=67) had ovarian cancer. The median length of hospital stay was 12 days (range 1–23), with a median overall survival after malignant bowel obstruction diagnosis of 7 months (range 0.1–64.1). Patients with active interventions had a longer length of stay compared with those with conservative management (13 vs 6 days, p<0.001). However, patients who received multiple active interventions had increased overall survival (9.1 vs 2.9 months, p=0.049). Conclusion: Patients who received multimodal treatment for malignant bowel obstruction had an increased length of stay and improvement in survival of over 6 months. This emphasizes the importance of a multidisciplinary approach to actively manage malignant bowel obstruction in advanced gynecologic cancer.